Notes on the text of Ovid’s Metamorphoses - Georg Luck (Exemplaria Classica, 2008)
The corruptions in the text of Ovid’s Metamorphoses are more frequent than the recent editors of the work have suspected. They (the editors) depend too much on a relatively small group of highly valued witnesses, instead of having followed the example of Heinsius and Burman. They should have looked at a larger number of witnesses and resorted more often to the emendatio ope ingenii. A great deal of work remains to be done, as a critical examination of thirty-one passages shows. Sometimes, only a different punctuation is needed; often, the solution of a problem was found long ago and then forgotten; in a few cases, new conjectures are offered. Some typical sources of corruption are identified.